miRNA-29b-3p: An Important Target for Ameliorating Liver Fibrosis in Wilson Disease by Inhibiting Autophagy - Huang, Peng; Huang, Yuzhe; Dong, Ting; Yang, Yulong; He, Wei; Wang, Meixia; Wang, Han; Yang, Wenming (Current Molecular Medicine, 2025)
<span class=
Keywords: ULK1